(untitled) (Development Service Industry Management, 2024)
The article substantiates the relevance of determining the functional components of financial and economic security management of business entities. It is established that the problems of effective management of financial and economic security of business entities are caused by the constant increase in the risks of economic activity, the presence and growth of which can lead to a significant decrease in the level of financial and economic status of business entities. The purpose of the article is to determine the functional components of financial and economic security management of business entities and the features of its provision in conditions of external and internal threats. It is noted that financial and economic security is an important part of the management of a business entity, which protects: the financial interests of the enterprise from harmful internal and external threats and the interests of owners; controls financial resources; has the ability to resist existing and future dangers that can cause significant economic damage. It is established that FES is one of the important characteristics of ensuring the protection of the activities of any business entity from the influence of negative factors of the external and internal environment and reflects the level of efficiency and stability of its functioning. In addition, assessing the financial condition of an enterprise and monitoring the use of its economic potential is a necessary condition for creating a system of financial and economic security for an enterprise. It is noted that the problem of managing the financial and economic security of a business entity in the present conditions and the practical implementation of its functional components has been and remains relevant for domestic enterprises, since the FES management system involves not only determining and tracking changes in the level of security in general, but also systematically improving the process of interaction between entities and security objects. As a result of the study of the functional components of managing the financial and economic security of business entities, a conclusion was made about the relationship between FES management and the financial activities of the enterprise, which made it possible to specify the FES objects and determine the range of priority tasks of security entities.